2022
DOI: 10.21608/eajbsd.2022.261160
|View full text |Cite
|
Sign up to set email alerts
|

Role of Psyllium Husk (Plantago ovata) on Liver Function Alterations Induced by Carbon Tetrachloride (CCl4) in Adult Male Albino Rats

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Numerous essential biological components, including proteins, nucleic acids, lipids, amino acids, and nucleotides, interact with the trichloromethyl free radical. The trichloromethyl peroxy radical is produced from the free trichloromethyl radical (Mostafa et al, 2022). The trichloromethyl peroxy radical is far more likely than the trichloromethyl free radical to take hydrogen from polyunsaturated fatty acids, which starts the process of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous essential biological components, including proteins, nucleic acids, lipids, amino acids, and nucleotides, interact with the trichloromethyl free radical. The trichloromethyl peroxy radical is produced from the free trichloromethyl radical (Mostafa et al, 2022). The trichloromethyl peroxy radical is far more likely than the trichloromethyl free radical to take hydrogen from polyunsaturated fatty acids, which starts the process of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that the intoxicated rats only got PSH for a brief period of time and that the amount of psyllium given to the CCl4+PS group was lower than that given to the PS+CCl4 group. ( Sharma & Shukla, 2011;Mostafa et al, 2022) found that the antioxidant was ineffective in treating the liver at low doses and that histology findings indicated modest generation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various sources of free radicals or superoxide radicals can be neutralized by antioxidant enzymes. In CCl4-induced oxidative stress rats, Mostafa, et al [54] showed that GNL reversed the expression of catalase, glutathione peroxidase, and glutathione-S-transferase, and reduced glutathione in the liver tissues [54]. GNL also reverses isoproterenol's suppression of catalase, glutathione peroxidase and glutathione-S-transferase activity, and mRNA expression [55].…”
Section: Glutathione Modulation By Gnlmentioning
confidence: 99%